Data Privacy for the Smart Grid - Rebecca Herold; Christine Hertzog (Auerbach Publications, 2015)
Privacy for the Smart Grid provides easy-to-understand guidance on data privacy issues and the implications for creating privacy risk management programs, along with privacy policies and practices required to ensure Smart Grid privacy. It addresses privacy in electric, natural gas, and water grids from two different perspectives of the topic, one from a Smart Grid expert and another from a privacy and information security expert. While considering privacy in the Smart Grid, the book also examines the data created by Smart Grid technologies and machine-to-machine applications.